Digital-Based Sales Transformation in Strengthening Economic Resilience - makmur, chesa; Ahmed, Nasheeta Shareen (Universitas Terbuka, 2023)
Covid-19 has become a global pandemic; this impacts all sectors, including the economic sector and people's buying interest. As a result, the sales process must also be carried out in their respective homes, so in this case, they have undergone a transformation based on digital technology. This study aims to describe the sales process strategy during the Covid-19 Pandemic and Post-Covid-19 Pandemic, find out the forms of media and methods used in digital-based sales and purchases, and examine the challenges faced in digital-based sales, and identify the impact of sales digital-based to economic resilience. This study uses a qualitative approach. Design The research used in this study is phenomenology. Qualitative research data is descriptive; this data is presented in words, pictures, and tables at the research location used in Surabaya City, East Java Province. The informants of this research were determined using purposive sampling chosen with specific considerations and goals. Data collection techniques used in this study were observation, in-depth interviews, focus group discussion (FGD), and documentation. In this study it was found that traders needed to have a new strategy to continue marketing their wares during the Covid-19 pandemic and post-covid-19 pandemic. This new strategy became a new opportunity and added income because they could sell online and offline. Furthermore, there needs to be an increase in the quality control of merchandise so that buyers feel safe buying and transacting.